PENERAPAN PEMBELAJARAN KOOPERATIF TEKNIK BERKIRIM SALAM DAN SOAL DISERTAI TEKNIK DUA TINGGAL DUA TAMU TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 11 PADANG - Lestari, Siti; Rahmi, Rahmi; febriana, Rian (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This research was conducted based on the fact indicating that the studentsâ understanding of mathematic concept was still low, the students canât give information with another students. The aim of this research was to improve the studentsâ understanding of mathematic concept by using chained-greeting and question technique accompanied with two stay two stray technique in class VIII of SMPN 11 Padang. This was an experimental research whose sample was chosen by random. The instruments of the research was a test on the studentsâ understanding on mathematicÂ concept. The result of the research revealed that after the strategy applied, their understanding on mathematicÂ concept was not better than that of students treating by using conventional learning strategy. This could be seen from the t-value is 0,829 which was smaller than t = 1,669. Thus it was concluded that the use of chained-greeting and question technique accompanied with two stay two stray technique could improve the students understanding of mathematic concept not better than that of the conventional learning.Â